2019
DOI: 10.1051/e3sconf/201911201014
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of cycle variability at the Diesel engine fuelled with animal fats

Abstract: The progressive diminution of the oil reserves all over the world highlights the necessity of using alternative fuels derived from durable renewable resource. The use of the alternative fuels represents a viable solution to reduce the pollutant emissions and to replace fossil fuels. Thus, a viable solution is the use of the animal fats in mixture with the diesel fuel at the diesel engines. A D2156 MTN8 diesel engine was firstly fuelled with diesel fuel and then with different blends of diesel fuel-animal fats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It can be concluded that the test engine worked correctly under all analysed conditions and did not exceed the permissible stability indices for internal combustion reciprocating engines. According to Nicolici et al, 39 the acceptable COV pmax limit for internal combustion engines is 10% and is equal to the limit that is acceptable until recently for COV IMEP . 40 Currently, the COV IMEP limit for internal combustion engines defined by Heywood is 5%.…”
Section: Engine Stabilitymentioning
confidence: 92%
“…It can be concluded that the test engine worked correctly under all analysed conditions and did not exceed the permissible stability indices for internal combustion reciprocating engines. According to Nicolici et al, 39 the acceptable COV pmax limit for internal combustion engines is 10% and is equal to the limit that is acceptable until recently for COV IMEP . 40 Currently, the COV IMEP limit for internal combustion engines defined by Heywood is 5%.…”
Section: Engine Stabilitymentioning
confidence: 92%